Thoroughly grasping the viewpoints of the party's 13th congress on economic development - Nguyễn Hồ Thanh, (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
The document of the 13th National Congress of Deputies is built based on a profound summary of theory and practice; crystallizes the wisdom, will, and aspirations of the entire Party, people, and army. Therefore, grasping the content of the Party's viewpoint is of special importance. The article thoroughly grasps some basic contents in the Document of the 13th National Congress of Deputies on economic development. On that basis, propose several solutions to effectively implement the view of the 13th Party Congress on economic development in the coming time.